2016
DOI: 10.1111/ecc.12544
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the factors associated with positive experiences in carers of someone with cancer

Abstract: The aim of this review was to identify the factors associated with positive experiences in non-professional carers of someone with a cancer diagnosis. A systematic search of the following electronic databases was undertaken: Cochrane Library, CINAHL, PsycINFO, SocINDEX and Medline. Literature was searched using terms relating to cancer, caring and positive experiences. Additional records were identified through a manual search of relevant reference lists. The search included studies published in English from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 81 publications
1
21
0
2
Order By: Relevance
“…Geng et al (2018) reviewed studies on the negative experiences of family caregivers of cancer patients and found that cancer caregivers were especially vulnerable to depression. Compared to research on negative experiences of caregiver, there is less known research on the positive experiences such as the improvement of caregiver-patient relations, feeling rewarded, and a sense of personal growth and worth (Young and Snowden, 2016). In addition, most prior studies were focused on family caregivers who were caring for cancer patients at home but failed to explore them in hospital settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geng et al (2018) reviewed studies on the negative experiences of family caregivers of cancer patients and found that cancer caregivers were especially vulnerable to depression. Compared to research on negative experiences of caregiver, there is less known research on the positive experiences such as the improvement of caregiver-patient relations, feeling rewarded, and a sense of personal growth and worth (Young and Snowden, 2016). In addition, most prior studies were focused on family caregivers who were caring for cancer patients at home but failed to explore them in hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…Social support plays a key role in cancer family caregivers' psychological experiences, which has been well established in some studies. Cancer caregivers with a high level of social support expressed low level of depression (Ustaalioglu et al, 2018) and high level of positive experiences (Young and Snowden, 2016). Thus, individuals with insecure attachment style might perceive a low level of social support, which make them experience high depression and low self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Patients do not want to be seen as being demanding or “difficult”, even when in considerable need, so there is a global unmet need for information, social, emotional, and psychological support . Many people with financial problems and practical issues such as transport, parking, and getting around generally lack the support they need …”
Section: Introductionmentioning
confidence: 99%
“…14 Many people with financial problems and practical issues such as transport, parking, and getting around generally lack the support they need. 15 The financial burden of a cancer diagnosis is becoming better understood. 2 In UK, poorer people are at risk of losing their homes.…”
Section: Introductionmentioning
confidence: 99%
“…The act of caring is based on personal and cultural values that give meaning to caregiving (Yamaguchi, Cohen, & Uza, ). For this reason, it is not uncommon for caregivers to report positive experiences, such as more intimate relationships, more empathy with others and greater appreciation of life (Mosher, Adams, et al, ; Young & Snowden, ). However, caring for a family member with cancer is a challenging experience that requires an adjustment to change (Teskereci & Kulakac, ), adaptation to daily care tasks and to a new lifestyle (Ellis et al, ).…”
Section: Introductionmentioning
confidence: 99%